Broiler Chicken Coop Heating Efficiency Analysis: Comparative Study of Heat Dispersion and Energy Consumption - Utomo, Archi Kun Cahyo; Danuarta, Dimas Zulfa; Triatmaja, Fidelis Gigih; Armunanto, Vincentius Bram; Suyanto (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
Broiler house heaters play a crucial role in maintaining optimal temperatures during the brooding phase to support optimal growth. However, conventional heaters such as the Super Saver Heater and Heater Handmade have limitations in terms of energy efficiency and heat distribution. This study aims to analyze the performance of the proposed heater in three key aspects: heating rate, heat distribution, and fuel consumption efficiency, and compare it with conventional heaters. The results indicate that the proposed heater increased the temperature from 26°C to 53°C within 2 minutes, with an average heating rate of 13.5°C per minute, outperforming conventional heaters. Heat distribution was more uniform, ensuring stable temperatures at various measurement points within the broiler house. In terms of energy efficiency, the proposed heater consumed only 0.5 kg of LPG in 6 minutes, significantly lower than the Super Saver Heater, which required 1 kg of LPG. Overall, the proposed heater demonstrated superior energy efficiency, faster heating, and more stable heat distribution, making it a more effective alternative to conventional heating systems used in broiler farming.